The Natural History of Efforts to Stop Smoking: A Prospective Cohort Study - Hughes, John R. (2012)
BACKGROUND: In a prior study, we found changing tobacco use was more complex than previously thought, with users often transitioning between intending to quit and not intending to quit, and among typical use, abstinence, and reduction, on multiple occasions. The current study attempted to replicate those results. METHODS: A convenience sample of 40 tobacco smokers who intended to quit within the next 3 months called in nightly for 28 days to an Interactive Voice Response system to report cigs/day and daily intentions to smoke or not for the next day. We provided no treatment. RESULTS: Within the month of the study, 32% of smokers had multiple episodes of intentions to not smoke, and 64% transitioned among smoking as usual, abstinence, and reduction status on multiple occasions. When participants reported they intended to not smoke the next day, 56% of the time they did not make a quit attempt the next day. Just under half (44%) of quit attempts occurred on days with no intentions to quit the night before. Most quit attempts (69%) lasted less than a day. Reduction in cigs/day was as common as abstinence. CONCLUSIONS: Our prospective results replicated retrospective findings that most attempts to stop smoking result in a complex pattern of changes in smoking. These results suggest future research on treatments that can accommodate a) multiple quit attempts over a short period, b) reduction episodes, c) unplanned quit attempts, and d) immediate relapse.